ANTI-DUMPING MEASURE AS TRADE REMEDY: THE DOMINATION OF INTERNATIONAL TRADE DISPUTES - Gea, Gita Venolita Valentina (Universitas Internasional Batam, 2023)
WTO as the only international organization in the scope of public international trade also governs on dumping which found both on the GATT and Anti Dumping Agreement (ADA). Anti-dumping measures may applied as a trade remedy by a state member against other state member accused for practicing dumping. However, former research found that the number of trade disputes before the DSB WTO were mostly caused by anti-dumping measures and turned out that those measures were violating the regulations. This research aims to figure out on how does anti-dumping measures contribute on the escalation and domination of the international trade disputes. Findings from this research shows that before imposing an anti-dumping measure, the state members may determine the practice of dumping practice. The determination is self-claimed under the national authority and later the state may impose temporary anti-dumping measures. After complaints filed to the DSB WTO by the accused state, it is often proved that no dumping practice was ever carried out and the anti-dumping measures turned out to be a violation. This one-sided claim with no third party to re-examine and give approval, may cause further injuries and disrupts the climate of international trade. Hence, the WTO needs to play its role on figuring out and providing a new way out.